(untitled) (Altre Modernità, 2020)
In an attempt to open a conversation on the remnant, this essay proceeds as a collection of notes on the following topics: 1) Definitions of flotsam and jetsam 2) Some famous figures of waste: Defoe, Melville, Twain, myth of Hercules, A.C. Bradley, Trotsky, Walter Benjamin 3) Waste in contemporary fiction and media, with readings of some touchstone passages 4) Found materials and residues as subjects in the visual arts 5) Two final images of flotsam Underlying the discussion of these particulars are three themes based on common reactions to remnants, waste, trash, flotsam and jetsam: devastation, abjection, and bricolage.